Extrapontine Myelinolysis of Osmotic Demyelination Syndrome in a Case of Postoperative Suprasellar Arachnoid Cyst - Peng Zhao; Xuyi Zong; Xinsheng Wang; Yazhuo Zhang (Case Reports in Medicine)
The extrapontine myelinolysis of osmotic demyelination syndrome (ODS) is a well-known but uncommon disorder of the central nervous system. Although the mechanism is not fully understood and the treatment is controversial, hyponatremia is probably considered to be the main pathophysiological basis. There are few reports of ODS caused by a sellar lesion. Here we present a case of suprasellar arachnoid cyst that developed extrapontine myelinolysis of ODS after a neuroendoscopic treatment procedure. It is suggested that patients with suprasellar lesions are at risk of developing extrapontine myelinolysis of ODS and correction of hyponatremia in these cases should be closely monitored.